Low-carbon recycled sand concrete and preparation method thereof

By using a combination of carbon dioxide curing and reinforcement additives in the concrete, the flowability and strength of waste concrete recycled sand concrete is improved, the problems of high cement addition and insufficient performance are solved, and a low-carbon and environmentally friendly concrete regeneration cycle is achieved.

CN118619630BActive Publication Date: 2024-12-27CHINA CONSTR WESTERN CONSTR (GUANGDONG) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410841744.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2024-12-27
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

The amount of cement added to existing concrete materials is high, the recycled sand concrete prepared by regeneration of waste concrete has poor fluidity, and the strength and water absorption performance need to be improved.

Method used

The preparation method of low-carbon recycled sand concrete includes treating large-particle aggregates and recycled fine aggregates in a carbon dioxide curing environment, combining silicate cement and volcanic ash, using sodium silicate, sodium sulfate and calcium hydroxide as reinforcement Additives, improve aggregate activity through crushing, calcining and activation processes, reduce water absorption and increase strength.

Benefits of technology

It improves the fluidity and strength of concrete, reduces carbon emissions, realizes efficient regeneration cycle of waste concrete, meets the requirements of green, low-carbon and environmental protection, and improves the mechanical properties and durability of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619630B_ABST
    Figure CN118619630B_ABST
Patent Text Reader

Abstract

The invention discloses a low-carbon recycled sand concrete and a preparation method thereof, which belongs to the technical field of concrete materials and is used to solve the technical problems in the prior art that the amount of cement added in concrete materials is high, the fluidity of concrete materials prepared by recycled sand prepared by crushing waste concrete is poor, and the strength and water absorption performance of concrete specimens need to be further improved. The invention comprises the following components in parts by weight: 60-80 parts of recycled mixed aggregate, 80-100 parts of coarse aggregate, 20-30 parts of cement mixture, 8-12 parts of reinforcing additive, 0.5-1 part of water reducer and 25-30 parts of water. The invention realizes the recycling of waste concrete and reduces carbon emission in the concrete production process by regenerating and recycling waste concrete and then coordinating with coarse aggregate, cement mixture and reinforcing additive, thereby improving the fluidity of concrete materials and the mechanical properties and durability of concrete specimens.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, and in particular to a low-carbon recycled sand concrete and a preparation method thereof. Background Art

[0002] Concrete is a general term for engineering composite materials that are made of aggregates bonded together by cementitious materials. The term concrete usually refers to cement as a cementitious material, sand and stone as aggregates, mixed with water in a certain proportion, and obtained by mixing. It is also called ordinary concrete and is widely used in civil engineering. With the increasing severity of global climate change and environmental problems, low-carbon, environmental protection, and sustainable development have become the keywords for the development of all walks of life. In the construction industry, concrete is the most basic and largest building material, and the carbon emission problem during its production and use is particularly prominent.

[0003] The high carbon emissions of concrete mainly come from the production and use of cement. Since the cement production process involves the calcination of raw materials such as limestone, it consumes a lot of energy and resources. It also emits a large amount of greenhouse gases such as carbon dioxide, which has a negative impact on the environment. Therefore, the cement industry is a veritable carbon emitter, which also leads to high carbon emissions of concrete. In order to reduce the amount of cement used in concrete, mineral materials are usually added to cement, but the large addition of mineral materials leads to a decrease in the strength of concrete.

[0004] Recycled sand concrete is usually made from sand through processes such as mechanical crushing and screening. Compared with traditional natural sand, the energy consumption and emissions in the production process of recycled sand are lower, and it has better environmental performance. However, the water absorption rate of recycled sand is high, especially the recycled sand prepared by recycling waste concrete. Due to its high hygroscopicity, the fluidity of concrete is poor. In addition, the porosity of recycled sand prepared by recycling waste concrete is high, and its own strength is poor, resulting in the need to further improve the strength and water absorption of concrete.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a low-carbon recycled sand concrete and a preparation method thereof, so as to solve the technical problems in the prior art that the amount of cement added in the concrete material is high, the fluidity of the concrete material prepared by the recycled sand prepared by recycling waste concrete is poor, and the strength and water absorption performance of the concrete specimen need to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: a low-carbon recycled sand concrete, comprising the following components in parts by weight: 60-80 parts of recycled mixed aggregate, 80-100 parts of coarse aggregate, 20-30 parts of cement mixture, 8-12 parts of reinforcing additive, 0.5-1 part of water reducing agent and 25-30 parts of water;

[0008] The preparation method of the recycled mixed aggregate is:

[0009] A1. Evenly mix the large-size aggregate and the recycled fine aggregate to obtain mixed aggregate;

[0010] A2. Transfer the mixed aggregate to a curing box filled with carbon dioxide at a temperature of 20-25°C, a humidity of 60-70%, and a pressure of 0.5-0.8MPa, and cure for 30-50 hours to obtain recycled mixed aggregate.

[0011] The synthetic reaction principle of recycled mixed aggregate is:

[0012] When large-size aggregate is prepared, its surface contains a large amount of new cementing substances formed by the reaction of silicate minerals and alkali. The recycled fine aggregate contains substances such as calcium hydroxide and hydrated silicate. During the carbon dioxide curing process of the mixed aggregate, the carbon dioxide can react with the new cementing species on the large-size aggregate or the calcium hydroxide, hydrated silicate and other substances in the recycled fine aggregate, increase the solid phase volume of the aggregate, fill the pores in the mixed aggregate, reduce the channels for water to enter the interior of the concrete, and make the concrete more compact, thereby reducing the water absorption rate of the concrete and improving its compressive strength.

[0013] Further, the cement mixture is composed of ordinary Portland cement and volcanic ash in a weight ratio of 3:1, and the particle size of the volcanic ash is 10-50 μm;

[0014] The reinforcing agent is composed of sodium silicate, sodium sulfate and calcium hydroxide in a weight ratio of 5:3:1;

[0015] The particle size of the coarse aggregate is 20-35 mm;

[0016] The water reducer is a polycarboxylate water reducer.

[0017] Furthermore, in step A1, the weight ratio of the large-size aggregate to the recycled fine aggregate is 1-2:3-5.

[0018] Further, the large-size aggregate is processed by the following steps:

[0019] B1. Use a crusher to remove iron from the waste concrete, then wash and dry it to obtain concrete particles with a particle size of less than 10 cm;

[0020] B2. The concrete particles are transferred to a muffle furnace, the temperature of the muffle furnace is increased to 450-550°C at a heating rate of 2-8°C / min, and the temperature is kept for 3-5 hours to obtain calcined particles;

[0021] B3, directly adding the calcined particles into the low-temperature activation liquid while they are still hot, and post-treating to obtain activated particles;

[0022] B4. Add the activated particles into the drum screen for screening to obtain large-size aggregates with a particle size of 1-3 cm and small-size aggregates with a particle size of less than 1 cm.

[0023] The principle of preparing large-size aggregate and small-size aggregate from waste concrete is:

[0024] By crushing concrete materials into particles of relatively uniform size, the surface area of ​​concrete particles is increased to facilitate uniform heating during calcination. During the cooling treatment of the activation liquid, the activation liquid can penetrate into the pores and cracks of the concrete particles, react with the minerals therein, weaken the binding force between aggregate and sand and gravel, clean off impurities and attachments on the surface of the aggregate, and promote the separation of sand and gravel in the concrete. In addition, during the treatment of the high-temperature concrete particles with the activation liquid, the silicate minerals on the surface of the concrete particles can react with alkali to form new substances with gelling properties, thereby increasing the activity of the aggregate. The drum screen is selected to screen the aggregate, and the mutual impact of the aggregate in the drum screen can further promote the separation and dispersion of the sand and gravel that make up the concrete, thereby obtaining large-size aggregate and small-size aggregate.

[0025] Furthermore, in step B3, the activation solution is composed of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and 0.1-0.5 mol / L sodium hydroxide solution in a dosage ratio of 1-2g:3-5g:200mL, the temperature of the activation solution is 10-20°C, and the post-treatment includes: after the soaking is completed, filtering, washing the filter cake with purified water for 3 times, and drying naturally to obtain activated particles.

[0026] Further, the recycled fine aggregate is processed by the following steps:

[0027] C1. Add small-size aggregate into a crusher, crush it, and pass it through a 20-mesh sieve to obtain recycled powder;

[0028] C2, mixing the recycled powder and the auxiliary powder evenly to obtain a mixed powder;

[0029] C3, adding the mixed powder and the mixed acid solution into a granulator for granulation to obtain mixed particles;

[0030] C4, transferring the mixed particles to a curing box at a temperature of 22-26°C and a humidity of 65-75% for 3 days to obtain cured particles;

[0031] C5. Transfer the cured particles to a muffle furnace, raise the temperature of the muffle furnace to 900-1000°C, keep it warm for 2-3 hours, naturally cool it to room temperature, and post-treat it to obtain recycled fine aggregate.

[0032] The synthetic reaction principle of recycled fine aggregate is:

[0033] By crushing and sieving small-size aggregates, a recycled powder with a relatively uniform particle size is obtained, which is mixed with auxiliary powder and mixed acid solution for granulation, and subjected to oxidation and calcination treatment to obtain a high-strength recycled fine aggregate; by optimizing the dosage ratio of the recycled powder, auxiliary powder and mixed acid solution, the mixed acid in the mixed particles can promote the hydration reaction of the constituent particles of the mixed particles when the mixed particles are cured in a low-temperature, high-humidity curing environment, so that the mixed particles complete preliminary bonding and curing, and obtain cured particles with a certain strength; during the high-temperature calcination process, the mixed acid can also chemically react with the minerals in the particles to form a new crystal structure or compound, thereby improving the hardness and strength of the particles.

[0034] Furthermore, in step C2, the weight ratio of the regenerated powder to the auxiliary powder is 5:2-3, and the auxiliary powder is composed of nano calcium oxide, nano silicon dioxide, and fly ash in a weight ratio of 7-8:2-3:5-6; in step C3, the amount ratio of the mixed powder to the mixed acid solution is 3g:1mL, and the mixed acid solution is composed of boric acid, oxalic acid and water in a dosage ratio of 3-5g:0.8-1.2g:20mL; in step C5, the heating program of the muffle furnace is: the muffle furnace is first heated at a heating rate of 4-6°C / min The temperature is raised to 80-90°C, kept warm for 5-8 minutes, then raised to 100-110°C at a heating rate of 1-2°C / min, kept warm for 20-30 minutes, then raised to 500-550°C at a heating rate of 6-8°C / min, kept warm for 30-50 minutes, then raised to 900-1000°C at a heating rate of 5-8°C / min. The post-treatment includes: transferring the calcined particles to a drum screen with a screen diameter of 2mm, rolling screening, removing micro powder impurities with a particle size of less than 2mm, and obtaining recycled fine aggregate.

[0035] Furthermore, the granulation method of the mixed particles in step C3 is: adding 2 / 3-3 / 4 parts by weight of the mixed powder to a disc granulator, setting the inclination angle of the disc granulator to 10-15°, the rotation speed to 12-16r / min, slowly adding the mixed acid solution to the disc granulator under mixing, mixing for 30-50min, adding the remaining mixed powder to the disc granulator, maintaining mixing and granulating for 10-15min, and obtaining mixed particles with a particle size of 2-10mm.

[0036] The present invention also provides a method for preparing low-carbon recycled sand concrete, comprising the following steps:

[0037] S1, mixing the enhancing agent and water evenly to obtain an enhancing agent aqueous solution;

[0038] S2. Add recycled mixed aggregate, coarse aggregate, cement mixture and water reducing agent into a mixer and mix for 5-7 minutes. Under stirring, add the auxiliary agent aqueous solution into the mixer and mix for 10-15 minutes to obtain recycled sand concrete.

[0039] The present invention has the following beneficial effects:

[0040] 1. The low-carbon recycled sand concrete of the present invention uses waste concrete as a material, regenerates it to prepare recycled fine aggregate and large-size aggregate, treats it in a carbon dioxide curing environment, and then cooperates with coarse aggregate, cement mixture, and reinforcing additives to improve the fluidity of concrete materials and the strength and durability of concrete specimens, thereby preparing a high-strength concrete system and realizing the recycling of waste concrete; by adding volcanic ash mineral materials to cement, the amount of cement is reduced, and the amount of cement in the concrete system is reduced, thereby reducing carbon emissions in the concrete production process, meeting green and low-carbon environmental protection requirements.

[0041] 2. The low-carbon recycled sand concrete of the present invention uses waste concrete as a recycled base material, and promotes the separation of sand and gravel aggregates in concrete particles through crushing, calcining and activation, which is beneficial to breaking up the sand and gravel constituting the concrete material and facilitating its recycling and reuse. After the small-size aggregate is crushed and mixed with auxiliary powder and mixed acid solution for granulation, the particles of the recycled fine aggregate are promoted to solidify and cross-link, and the self-strength of the recycled fine aggregate is improved through curing and calcining treatment. The recycled fine aggregate and the large-size aggregate are treated in a carbon dioxide curing environment. Since carbon dioxide reacts with calcium hydroxide, hydrated silicate and other substances in the aggregate, the pores in the coagulated aggregate are filled, and the channels for water to enter the interior of the concrete are reduced, thereby reducing the water absorption rate of the concrete and improving the mechanical strength and fluidity of the concrete material. In addition, due to the pre-treatment with carbon dioxide, the calcium hydroxide in the concrete can be promoted to react to form calcium carbonate, and the carbonization depth of the concrete is reduced to a certain extent, thereby improving the durability of the concrete material.

[0042] 3. The low-carbon regenerated sand concrete of the present invention is prepared by combining a reinforcing agent composed of sodium silicate, sodium sulfate and calcium hydroxide with a cement composed of silicate cement and volcanic ash. The reinforcing agent enters the concrete system in the form of a solution. On the one hand, it supplements the lack of calcium hydroxide and silicate in the concrete material caused by carbonization of carbon dioxide. On the other hand, the reinforcing agent is dispersed in the solution with extremely fine fineness, and has a good filling effect in the concrete material, thereby increasing the fluidity of the concrete. Sodium sulfate can stimulate the activity of silicate cement and volcanic ash, so that they can produce a synergistic effect with sodium silicate, further improving the mechanical properties of the concrete material. In addition, since silicate cement concrete has a smaller porosity and higher strength, it can cooperate with a small molecule reinforcing agent to further reduce the porosity of the concrete, so that the concrete has good durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 The figure is a flowchart of the process for preparing low-carbon recycled sand concrete according to the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] See also Figure 1 This embodiment provides a method for preparing low-carbon recycled sand concrete, comprising the following steps:

[0048] S1. Preparation of large-size aggregate and small-size aggregate

[0049] After iron removal and crushing of the waste concrete using a crusher, washing and drying are performed to obtain concrete particles with a particle size of less than 10 cm;

[0050] The concrete particles were transferred to a muffle furnace, the temperature of the muffle furnace was increased to 450°C at a heating rate of 2°C / min, and the temperature was kept for 3 hours to obtain calcined particles;

[0051] Mix sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and 0.1 mol / L sodium hydroxide solution in a dosage ratio of 1g:3g:200mL to obtain an activation solution for later use;

[0052] The calcined particles were directly added to the activation solution at a temperature of 10°C while still hot, soaked for 20 minutes, filtered, and the filter cake was washed with purified water for 3 times and dried naturally to obtain activated particles;

[0053] The activated particles are added to the drum screen for screening to obtain large-size aggregates with a particle size of 1-3 cm and small-size aggregates with a particle size of less than 1 cm.

[0054] S2. Preparation of mixed particles

[0055] Add small-size aggregate into a pulverizer, pulverize, and pass through a 20-mesh sieve to obtain recycled powder;

[0056] Mix nano calcium oxide, nano silicon dioxide and fly ash in a weight ratio of 7:2:5 to obtain an auxiliary powder for later use;

[0057] The recycled powder and the auxiliary powder are mixed evenly in a weight ratio of 5:2 to obtain a mixed powder;

[0058] Mix boric acid, oxalic acid and water in a ratio of 3 g:0.8 g:20 mL to obtain a mixed acid solution for later use;

[0059] Weigh: 2 kg of mixed powder is added to the disc granulator, the inclination angle of the disc granulator is set to 10°, the rotation speed is 12 r / min, and under mixing, 1 L of mixed acid solution is slowly added to the disc granulator, and mixed for 30 min. The remaining 1 kg of mixed powder is added to the disc granulator, and the mixing and granulation is maintained for 10 min to obtain mixed particles with a particle size of 2-10 mm.

[0060] S3. Preparation of recycled fine aggregate

[0061] The mixed particles were transferred to a curing box at a temperature of 22° C. and a humidity of 65% and cured for 3 days to obtain cured particles;

[0062] The cured particles are transferred to a muffle furnace. The temperature of the muffle furnace is first increased to 80°C at a heating rate of 4°C / min, kept warm for 5 minutes, then increased to 100°C at a heating rate of 1°C / min, kept warm for 20 minutes, then increased to 500°C at a heating rate of 6°C / min, kept warm for 30 minutes, and then increased to 900°C at a heating rate of 5°C / min. The temperature is kept warm for 2 hours and naturally lowered to room temperature. The calcined particles are transferred to a drum sieve with a sieve diameter of 2 mm, and rolled for screening to remove micro-powder impurities with a particle size less than 2 mm to obtain recycled fine aggregate.

[0063] S4. Preparation of recycled mixed aggregate

[0064] The large-size aggregate and the recycled fine aggregate are uniformly mixed in a weight ratio of 1:3 to obtain a mixed aggregate;

[0065] The mixed aggregate was transferred to a curing box filled with carbon dioxide at a temperature of 20°C, a humidity of 60%, and a pressure of 0.5 MPa, and cured for 30 hours to obtain recycled mixed aggregate.

[0066] S5. Prepare materials

[0067] Ordinary Portland cement and volcanic ash are mixed in a weight ratio of 3:1 to obtain a cement mixture, wherein the particle size of the volcanic ash is 10-50 μm;

[0068] Mixing sodium silicate, sodium sulfate and calcium hydroxide in a weight ratio of 5:3:1 to obtain a reinforcing agent;

[0069] Crushed stone with a particle size of 20-35 mm was selected as coarse aggregate.

[0070] S6. Preparation of recycled sand concrete

[0071] Weigh: 0.8 kg of reinforcing agent and 2.5 kg of water and mix them evenly to obtain an aqueous solution of reinforcing agent;

[0072] Weigh: 6 kg of recycled mixed aggregate, 8 kg of coarse aggregate, 2 kg of cement mixture, and 50 g of polycarboxylate water reducer, add them into a mixer and mix for 5 minutes. Under stirring, add the auxiliary agent aqueous solution into the mixer and mix for 10 minutes to obtain recycled sand concrete.

[0073] Example 2

[0074] See also Figure 1 This embodiment provides a method for preparing low-carbon recycled sand concrete, comprising the following steps:

[0075] S1. Preparation of large-size aggregate and small-size aggregate

[0076] After iron removal and crushing of the waste concrete using a crusher, washing and drying are performed to obtain concrete particles with a particle size of less than 10 cm;

[0077] The concrete particles were transferred to a muffle furnace, the temperature of the muffle furnace was increased to 500°C at a heating rate of 5°C / min, and the temperature was kept for 4 hours to obtain calcined particles;

[0078] Sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and 0.3 mol / L sodium hydroxide solution were mixed in a dosage ratio of 1.5 g:4 g:200 mL to obtain an activation solution for later use;

[0079] The calcined particles were directly added to the activation solution at a temperature of 15°C while still hot, soaked for 25 minutes, filtered, and the filter cake was washed with purified water for 3 times and dried naturally to obtain activated particles;

[0080] The activated particles are added to the drum screen for screening to obtain large-size aggregates with a particle size of 1-3 cm and small-size aggregates with a particle size of less than 1 cm.

[0081] S2. Preparation of mixed particles

[0082] Add small-size aggregate into a pulverizer, pulverize, and pass through a 20-mesh sieve to obtain recycled powder;

[0083] Mix nano calcium oxide, nano silicon dioxide and fly ash in a weight ratio of 7.5:2.5:5.5 to obtain an auxiliary powder for later use;

[0084] The recycled powder and the auxiliary powder are mixed evenly in a weight ratio of 2:1 to obtain a mixed powder;

[0085] Mix boric acid, oxalic acid and water in a ratio of 4g:1g:20mL to obtain a mixed acid solution for later use;

[0086] Weigh: 2.2 kg of mixed powder is added to the disc granulator, the inclination angle of the disc granulator is set to 13°, the rotation speed is 14 r / min, and under mixing, 1 L of mixed acid solution is slowly added to the disc granulator, and mixed for 40 min. The remaining 0.8 kg of mixed powder is added to the disc granulator, and the mixing and granulation is maintained for 13 min to obtain mixed particles with a particle size of 2-10 mm.

[0087] S3. Preparation of recycled fine aggregate

[0088] The mixed particles were transferred to a curing box at a temperature of 24° C. and a humidity of 70% and cured for 3 days to obtain cured particles;

[0089] The cured particles were transferred to a muffle furnace, which was first heated to 85°C at a heating rate of 5°C / min and kept warm for 6 minutes, then heated to 105°C at a heating rate of 2°C / min and kept warm for 25 minutes, then heated to 530°C at a heating rate of 7°C / min and kept warm for 40 minutes, then heated to 950°C at a heating rate of 7°C / min and kept warm for 2.5 hours, and then naturally cooled to room temperature. The calcined particles were transferred to a drum sieve with a sieve diameter of 2 mm, and rolled for screening to remove micro-powder impurities with a particle size less than 2 mm to obtain recycled fine aggregate.

[0090] S4. Preparation of recycled mixed aggregate

[0091] The large-size aggregate and the recycled fine aggregate are uniformly mixed in a weight ratio of 1.5:4 to obtain a mixed aggregate;

[0092] The mixed aggregate was transferred to a curing box filled with carbon dioxide at a temperature of 23°C, a humidity of 65%, and a pressure of 0.7 MPa, and cured for 40 hours to obtain recycled mixed aggregate.

[0093] S5. Prepare materials

[0094] Ordinary Portland cement and volcanic ash are mixed in a weight ratio of 3:1 to obtain a cement mixture, wherein the particle size of the volcanic ash is 10-50 μm;

[0095] Mixing sodium silicate, sodium sulfate and calcium hydroxide in a weight ratio of 5:3:1 to obtain a reinforcing agent;

[0096] Crushed stone with a particle size of 20-35 mm was selected as coarse aggregate.

[0097] S6. Preparation of recycled sand concrete

[0098] Weigh: 1.0 kg of reinforcing agent and 2.7 kg of water and mix them evenly to obtain an aqueous solution of reinforcing agent;

[0099] Weigh: 7 kg of recycled mixed aggregate, 9 kg of coarse aggregate, 2.5 kg of cement mixture, and 75 g of polycarboxylate water reducer, add them into a mixer and mix for 6 minutes. Under stirring, add the auxiliary agent aqueous solution into the mixer and mix for 13 minutes to obtain recycled sand concrete.

[0100] Example 3

[0101] See also Figure 1 This embodiment provides a method for preparing low-carbon recycled sand concrete, comprising the following steps:

[0102] S1. Preparation of large-size aggregate and small-size aggregate

[0103] After iron removal and crushing of the waste concrete using a crusher, washing and drying are performed to obtain concrete particles with a particle size of less than 10 cm;

[0104] The concrete particles were transferred to a muffle furnace, the temperature of the muffle furnace was increased to 550°C at a heating rate of 8°C / min, and the temperature was kept for 5 hours to obtain calcined particles;

[0105] Sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and 0.5 mol / L sodium hydroxide solution were mixed in a dosage ratio of 2g:5g:200mL to obtain an activation solution for later use;

[0106] The calcined particles were directly added to the activation solution at a temperature of 20°C while still hot, soaked for 30 minutes, filtered, and the filter cake was washed with purified water for 3 times and dried naturally to obtain activated particles;

[0107] The activated particles are added to the drum screen for screening to obtain large-size aggregates with a particle size of 1-3 cm and small-size aggregates with a particle size of less than 1 cm.

[0108] S2. Preparation of mixed particles

[0109] Add small-size aggregate into a pulverizer, pulverize, and pass through a 20-mesh sieve to obtain recycled powder;

[0110] Mix nano calcium oxide, nano silicon dioxide and fly ash in a weight ratio of 8:3:6 to obtain an auxiliary powder for later use;

[0111] The recycled powder and the auxiliary powder are mixed evenly in a weight ratio of 5:3 to obtain a mixed powder;

[0112] Mix boric acid, oxalic acid and water in a ratio of 5 g:1.2 g:20 mL to obtain a mixed acid solution for later use;

[0113] Weigh: 2.25 kg of mixed powder is added to the disc granulator, the inclination angle of the disc granulator is set to 15°, the rotation speed is 16 r / min, and under mixing, 1 L of mixed acid solution is slowly added to the disc granulator, and mixed for 50 min. The remaining 0.75 kg of mixed powder is added to the disc granulator, and the mixing and granulation is maintained for 15 min to obtain mixed particles with a particle size of 2-10 mm.

[0114] S3. Preparation of recycled fine aggregate

[0115] The mixed particles were transferred to a curing box at a temperature of 26° C. and a humidity of 75% and cured for 3 days to obtain cured particles;

[0116] The cured particles are transferred to a muffle furnace, and the temperature is first increased to 90°C at a heating rate of 6°C / min, kept warm for 8 minutes, then increased to 110°C at a heating rate of 2°C / min, kept warm for 30 minutes, then increased to 550°C at a heating rate of 8°C / min, kept warm for 50 minutes, and then increased to 1000°C at a heating rate of 8°C / min, kept warm for 3 hours, and naturally lowered to room temperature. The calcined particles are transferred to a drum sieve with a sieve diameter of 2 mm, and rolled for screening to remove micro-powder impurities with a particle size less than 2 mm to obtain recycled fine aggregate.

[0117] S4. Preparation of recycled mixed aggregate

[0118] The large-size aggregate and the recycled fine aggregate are uniformly mixed in a weight ratio of 2:5 to obtain a mixed aggregate;

[0119] The mixed aggregate was transferred to a curing box filled with carbon dioxide at a temperature of 25°C, a humidity of 70%, and a pressure of 0.8 MPa, and cured for 50 hours to obtain recycled mixed aggregate.

[0120] S5. Prepare materials

[0121] Ordinary Portland cement and volcanic ash are mixed in a weight ratio of 3:1 to obtain a cement mixture, wherein the particle size of the volcanic ash is 10-50 μm;

[0122] Mixing sodium silicate, sodium sulfate and calcium hydroxide in a weight ratio of 5:3:1 to obtain a reinforcing agent;

[0123] Crushed stone with a particle size of 20-35 mm was selected as coarse aggregate.

[0124] S6. Preparation of recycled sand concrete

[0125] Weigh: 1.2 kg of reinforcing agent and 3.0 kg of water and mix them evenly to obtain an aqueous solution of reinforcing agent;

[0126] Weigh: 8 kg of recycled mixed aggregate, 10 kg of coarse aggregate, 3 kg of cement mixture, and 100 g of polycarboxylate water reducer, add them into a mixer and mix for 7 minutes. Under stirring, add the auxiliary agent aqueous solution into the mixer and mix for 15 minutes to obtain recycled sand concrete.

[0127] Comparative Example 1

[0128] The difference between this comparative example and Example 3 is that in step S6, the recycled mixed aggregate is composed of crushed stone with a particle size of 1-3 cm and river sand with a particle size of 2-10 mm in a weight ratio of 2:5.

[0129] Comparative Example 2

[0130] The difference between this comparative example and Example 3 is that in step S3, the mixed particles obtained in step S2 are used to replace the curing particles in step S3 to prepare the recycled fine aggregate.

[0131] Comparative Example 3

[0132] The difference between this comparative example and Example 3 is that in step S4, the recycled mixed aggregate is replaced by mixed aggregate.

[0133] Comparative Example 4

[0134] The difference between this comparative example and Example 3 is that in step S6, no reinforcing auxiliary agent is added.

[0135] Performance Testing:

[0136] The slump of the recycled sand concrete prepared in Examples 1-3 and Comparative Examples 1-4 and the compressive strength, water absorption and durability of the concrete samples prepared from the recycled sand concrete after curing for 28 days were tested, wherein the slump of the sample was tested according to the standard GB / T 14902-2012 "Ready-mixed concrete" to test the slump grade of the recycled sand concrete, the compressive strength and water absorption of the concrete sample prepared from the recycled sand concrete were tested with reference to the standard GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the durability was tested according to the standard GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The specific test results are shown in Table 1:

[0137] Table 1- Performance test data of recycled sand concrete and concrete samples prepared from it

[0138]

[0139] Data Analysis:

[0140] Comparing and analyzing the data in Table 1 above, the slump grade of the concrete prepared by the present invention reaches S4, the compressive strength of the concrete sample reaches 68.1MPa, the water absorption rate is reduced to 4.1%, and the carbonization depth is reduced to 0.79mm. The performance test data are all better than those of the comparative example, indicating that the present invention uses waste concrete as raw material, recycles it and then cooperates with coarse aggregate, cement mixture and reinforcing additives, which not only realizes the recycling of waste concrete, reduces the amount of cement added, reduces carbon emissions in the concrete production process, meets the green and low-carbon environmental protection requirements, but also improves the fluidity of the concrete material, and makes the concrete sample prepared from the concrete have good mechanical properties and durability.

[0141] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0142] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0143] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-carbon recycled sand concrete, characterized in that: The invention comprises the following components in parts by weight: 60-80 parts of recycled mixed aggregate, 80-100 parts of coarse aggregate, 20-30 parts of cement mixture, 8-12 parts of reinforcing agent, 0.5-1 part of water reducing agent and 25-30 parts of water, wherein the reinforcing agent is composed of sodium silicate, sodium sulfate and calcium hydroxide in a weight ratio of 5:3:1; The preparation method of the recycled mixed aggregate is: A1. Evenly mix the large-size aggregate and the recycled fine aggregate to obtain a mixed aggregate; A2. Transfer the mixed aggregate to a curing box filled with carbon dioxide at a temperature of 20-25°C, a humidity of 60-70%, and a pressure of 0.5-0.8MPa, and cure for 30-50 hours to obtain recycled mixed aggregate; Large-size aggregate is obtained by the following steps: B1. Use a crusher to remove iron from the waste concrete, then wash and dry it to obtain concrete particles with a particle size of less than 10 cm; B2. The concrete particles are transferred to a muffle furnace, the temperature of the muffle furnace is increased to 450-550°C at a heating rate of 2-8°C / min, and the temperature is kept for 3-5 hours to obtain calcined particles; B3, directly adding the calcined particles into the activation solution at 10-20°C while still hot, and post-treating to obtain activated particles; B4. Add the activated particles to the drum screen for screening to obtain large-size aggregates with a particle size of 1-3 cm and small-size aggregates with a particle size of less than 1 cm; Recycled fine aggregate is obtained by the following steps: C1. Add small-size aggregate into a crusher, crush it, and pass it through a 20-mesh sieve to obtain recycled powder; C2, mixing the recycled powder and the auxiliary powder evenly to obtain a mixed powder; C3, adding the mixed powder and the mixed acid solution into a granulator for granulation to obtain mixed particles; C4, transferring the mixed particles to a curing box at a temperature of 22-26°C and a humidity of 65-75% for 3 days to obtain cured particles; C5. Transfer the cured particles to a muffle furnace, raise the temperature of the muffle furnace to 900-1000°C, keep it warm for 2-3 hours, naturally cool it to room temperature, and post-treat it to obtain recycled fine aggregate.

2. The low-carbon recycled sand concrete according to claim 1, characterized in that: The cement mixture is composed of silicate cement and volcanic ash in a weight ratio of 3:1, the particle size of the volcanic ash is 10-50 μm; the particle size of the coarse aggregate is 20-35 mm; and the water reducer is a polycarboxylate water reducer.

3. The low-carbon recycled sand concrete according to claim 1, characterized in that: In step A1, the weight ratio of the large-size aggregate to the recycled fine aggregate is 1-2:3-5.

4. The low-carbon recycled sand concrete according to claim 1, characterized in that: In step B3, the activation solution is composed of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and 0.1-0.5 mol / L sodium hydroxide solution in a dosage ratio of 1-2g:3-5g:200mL, the temperature of the activation solution is 10-20°C, and the post-treatment includes: after the soaking is completed, filtering, washing the filter cake with purified water for 3 times, and drying naturally to obtain activated particles.

5. The low-carbon recycled sand concrete according to claim 1, characterized in that: In step C2, the weight ratio of the regenerated powder to the auxiliary powder is 5:2-3, and the auxiliary powder is composed of calcium oxide, silicon dioxide, and fly ash in a weight ratio of 7-8:2-3:5-6; in step C3, the amount ratio of the mixed powder to the mixed acid solution is 3g:1mL, and the mixed acid solution is composed of boric acid, oxalic acid and water in an amount ratio of 3-5g:0.8-1.2g:20mL; in step C5, the heating program of the muffle furnace is: the muffle furnace is first heated to 80-90°C at a heating rate of 4-6°C / min, kept warm for 5-8min, then heated to 100-110°C at a heating rate of 1-2°C / min, kept warm for 20-30min, then heated to 500-550°C at a heating rate of 6-8°C / min, kept warm for 30-50min, and then heated to 900-1000°C at a heating rate of 5-8°C / min.

6. The low-carbon recycled sand concrete according to claim 1, characterized in that: The granulation method of the mixed particles in step C3 is as follows: 2 / 3-3 / 4 parts by weight of the mixed powder is added to a disc granulator, the inclination angle of the disc granulator is set to 10-15°, the rotation speed is 12-16r / min, and the mixed acid solution is slowly added to the disc granulator under mixing, and mixed for 30-50min, and the remaining mixed powder is added to the disc granulator, and the mixing and granulation is maintained for 10-15min to obtain mixed particles with a particle size of 2-10mm.

7. A method for preparing low-carbon recycled sand concrete according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing the enhancing agent and water evenly to obtain an enhancing agent aqueous solution; S2. Add recycled mixed aggregate, coarse aggregate, cement mixture and water reducing agent into a mixer and mix for 5-7 minutes. Under stirring, add the auxiliary agent aqueous solution into the mixer and mix for 10-15 minutes to obtain recycled sand concrete.